2016
DOI: 10.1007/s10068-016-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the antioxidant activity of methanolic and aqueous extracts from the fruiting bodies of an edible mushroom Pleurotus djamor

Abstract: antioxidant activities, total phenolic, and flavonoid contents of extracts were analyzed based on radical scavenging activities of methanol and aqueous extracts using 1,1-diphenyl-2-picryl-hydrazyl (DPPH), N,N-dimethyl-p-phenylenediamine (DMPD), total Fe reducing power, CUPRAC, phosphomolybdenum, metal chelating activity, and lipid peroxidation inhibition assays. Both extract types showed efficient radical scavenging activities against DPPH and DMPD radicals, ferric (Fe) and cupric (Cu) ion reducing powers, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
9
1
1
Order By: Relevance
“…Formation of free radicals play critical rules in the development of many disorders including cancer, neurodegeneration, cardiovascular, diabetes and autoimmune diseases . In the last two decades, extensive efforts have focused on identifying and characterizing potential therapeutic plants as natural antioxidants sources to reduce the free radical‐ and peroxide‐induced cell and tissue injuries . Therefore, different procedures have been implemented to investigate the potential antioxidant activity of crude plant oils and extracts .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of free radicals play critical rules in the development of many disorders including cancer, neurodegeneration, cardiovascular, diabetes and autoimmune diseases . In the last two decades, extensive efforts have focused on identifying and characterizing potential therapeutic plants as natural antioxidants sources to reduce the free radical‐ and peroxide‐induced cell and tissue injuries . Therefore, different procedures have been implemented to investigate the potential antioxidant activity of crude plant oils and extracts .…”
Section: Resultsmentioning
confidence: 99%
“…In the last two decades, extensive efforts have focused on identifying and characterizing potential therapeutic plants as natural antioxidants sources to reduce the free radical‐ and peroxide‐induced cell and tissue injuries . Therefore, different procedures have been implemented to investigate the potential antioxidant activity of crude plant oils and extracts . In this study, we have employed the commonly used DPPH · and ABTS ·+ radical scavenging and metal ion chelating activity (MICA) assays to evaluate the antioxidant potentials of F‐PSEO and D‐PSEO.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe 3+ reducing capacities of the compounds indicate their electron donating abilities. Because of these properties, some compounds may play a role in terminating the free radical chain by converting reactive free radical species into more stable non-radical ones [Sudha et al 2016]. In some studies it also reported that there was a strong correlation between the Fe 3+ reducing capacity and the inhibition of lipid peroxidation [Hinneburg et al 2006].…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, pode ser cultivado em faixa ampla de temperatura (26 °C a 35 °C) e umidade ambiental superior a 80% (Jegadeesh, Lakshmanan, Kab-Yeul, Sabaratnam, & Raaman, 2018). Nos últimos anos, pesquisas têm demonstrado que P. djamor tem potencial para aplicações biotecnológica e medicinal, além de ser alimento orgânico (Ragasa et al, 2016;Sudha et al, 2016). As características físicas, sensoriais e fisiológicas, além do consumo crescente de P. djamor, tem estimulado a realização de investigação com a finalidade de avaliar a adaptação dessa espécie em substratos alternativos para crescimento e produção de basidiomas (Satpal et al, 2017).…”
Section: Introductionunclassified